One Ring Fit to Rule Them All? An Analysis of Avatar Bodies and Customization in Exergames - Czerwonka, Sara; Alvarez, Adrian; McArthur, Victoria (Frontiers in Psychology, 2021)
With the growing popularity of exergames, researchers have noted the importance of presenting players with customizable avatars to encourage the long-term adoption of healthy behaviors offline. However, the “idealized” avatar bodies presented in avatar customization interfaces can represent limited body types and often problematically represent gender as binary. In this paper, we present a systematic analysis of the avatar customization interfaces of six console-based exergames. Results of our analysis indicate that customization options tend to be limited in exergames, especially with regard to body type and gender. Implications for avatar self-priming, self-identification, and healthy behavior adoption are discussed.